MATHematikula: The Use of Cinematic Mathematics Videos to Enhance Students' Numeracy Skills in the Least-Learned Competencies in Statistics and Probability - Crodua Jr., Jovito B.; Itaas, Estela C. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study investigated the effectiveness of MATHematikula, a cinematic mathematics video, in enhancing numeracy skills among senior high school students, particularly in the least-learned competency of Statistics and Probability. Utilizing an explanatory sequential mixed-method design, 50 participants were randomly assigned to either an experimental group, which received instruction supplemented with the cinematic video, or a control group taught using the traditional approach. A paired samples t-test revealed significant posttest score improvements in both groups, while analysis of covariance (ANCOVA) confirmed that the experimental group outperformed the control group, demonstrating the intervention’s effectiveness. Qualitative findings from interviews with 10 participants further highlighted their experiences with MATHematikula, including its ability to simplify learning, make lessons more engaging, and the technical challenges encountered. To cope with these challenges, students employed peer collaboration, resourcefulness, and self-motivation. Additionally, insights revealed that students actively engaged with the platform’s interactive features, utilized it as a learning tool, and expressed enthusiasm for promoting it to their peers. These findings reveal the potential of cinematic mathematics videos as an innovative pedagogical tool for improving student learning outcomes in mathematics.